Modulation of the Default Mode Network in First-Episode, Drug-Naïve Major Depressive Disorder via Acupuncture at Baihui (GV20) Acupoint - Deng, Demao; Liao, Hai; Duan, Gaoxiong; Liu, Yanfei; He, Qianchao; Liu, Huimei; Tang, Lijun; Pang, Yong; Tao, Jien (Frontiers in Human Neuroscience, 2016)
Background: Previous neuroimaging studies have revealed that acupuncture modulates the default mode network (DMN) in healthy subjects and patients with certain disorder. However, few studies have been performed to investigate whether or not acupuncture might modulate the DMN in patients with major depressive disorder (MDD). Thereby, the aim of the present study was to assess alterations of the DMN induced by acupuncture stimulation in patients with first-episode, drug-naïve MDD. Materials and Methods: 29 patients with first-episode, drug-naïve MDD and 29 healthy subjects were enrolled in this study. All the healthy subjects underwent 6-minute resting-state functional magnetic resonance imaging (R-fMRI) scan. While patients underwent acupuncture stimulation for 20-minute electro-acupuncture stimulation (EAS) at Baihui acupoint (GV20) and two 6-minute R-fMRI scans before and after EAS. Based on the precuneus/posterior cingulate cortex (PC/PCC) as the seed region, functional connectivity (FC) method was adopted to examine abnormal DMN in patients by comparing with healthy subjects and to evaluate the influence of EAS on intrinsic connectivity within the DMN in patients with MDD. Results: Compared to healthy subjects, MDD patients had abnormal DMN. Moreover, results showed that EAS at GV20 induced increased FC between the PC/PCC and bilateral anterior cingulate cortex(ACC), and decreased FC between the PC/PCC and left middle prefrontal cortex, left angualr gyrus and bilateral hippocampus/parahippocampus (HIPP/paraHIPP) in patients with MDD, which were the main brain regions showing significant differences between the patients and healthy subjects. Conclusions: Our findings provide imaging evidence to support that GV20-related acupuncture stimulation may modulate the DMN in patients with first-episode, drug-naïve MDD. This study may partly interpret the neural mechanisms of acupuncture at GV20 which is used to treat patients with MDD in clinical.